2017
DOI: 10.1016/j.psychres.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit/hyperactivity disorder and callous-unemotional traits as moderators of conduct problems when examining impairment in emerging adults

Abstract: This study examines attention-deficit/hyperactivity disorder (ADHD) and callous-unemotional (CU) traits as moderators of the association between conduct problems (CP) and young adult functioning. Young adults (n=283; Mage=20.82 years; 53.4% female), oversampled for attention and behavior problems, provided self-ratings of ADHD, CP, and CU, and adaptive functioning and psychopathology. ADHD and CU simultaneously moderated relationships between CP and family functioning, tobacco use, and internalizing symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…The present study revealed that maladaptive procrastination is not a categorical problem due to ADHD symptoms. This result, which focused on procrastination as a behavioral impairment, is inconsistent with an earlier finding suggesting that ADHD exacerbates the association between cognitive burden and stress responses ( Hirvikoski et al, 2009 ) and job functioning and conduct problems in young ADHD ( Babinski et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The present study revealed that maladaptive procrastination is not a categorical problem due to ADHD symptoms. This result, which focused on procrastination as a behavioral impairment, is inconsistent with an earlier finding suggesting that ADHD exacerbates the association between cognitive burden and stress responses ( Hirvikoski et al, 2009 ) and job functioning and conduct problems in young ADHD ( Babinski et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In ADHD, impairment and comorbidity with CD may be moderated by LPE characteristics, especially in delinquent [ 41 ] and antisocial behavior [ 42 ]. The association between ADHD, CD and LPE also impacts and moderates psychosocial impairment among young adults [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both ADHD and CUt tend to develop in early childhood (Willoughby et al, 2015).Nevertheless, data regarding the association between ADHD and CUt is still inconclusive ( (Blader et al, 2013;Burns, 2000;Colledge & Blair, 2001;Fowler et al, 2009;Frick et al, 2000;Kaplan & Cornell, 2004;Lee & Hinshaw, 2004;Northover et al, 2015). Moreover, there is very limited data regarding the relative contribution of ADHD and CUt to CP, with preliminary studies suggesting that CUt is associated with CP in later development independent of ADHD symptoms (Babinski et al, 2017;Jezior et al, 2016;Waller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%